Growth of Pinus taeda L. in the first years after high thinning - Thaila Heberle; Thiago Floriani Stepka; Mário Dobner Júnior; Marcos Felipe Nicoletti (Ciência Rural, 2025)
ABSTRACT: Given the importance of managing Pinus taeda to obtain various products, observing growth and response immediately after the first interventions can help identify the ideal thinning time. This study analyzed results in the first years after two interventions in Pinus taeda plantations, considering 7 highly-selective thinning intensities and a thinning-free control treatment. The number of trees, basal area, and dominant diameters were assessed between the ages of 4 and 10 years. The dominant diameter data were statistically compared using the Scott-Knott test at 95% probability. With light thinning in the early stages, the forest reached a basal area of around 50 m²ha-1 and a dominant diameter of 25 cm at 10 years. At the same age, moderate thinning resulted in a basal area of approximately 45 m2ha-1 and up to 30 cm in dominant diameter, with values of around 35 m2ha-1 and up to 35 cm, respectively, under heavy thinning. For light thinning, the basal area that represents the greatest increase in volume is close to 45 m2ha-1 at between 4 and 5 years, while for moderate and heavy treatments, this value was reached between 5 and 6 years, with 41 and 31 m²ha-1, respectively. Moderate management allows the forest to continue developing in larger basal areas, thereby slightly delaying the next intervention without negatively affecting growth rates.